THE EFFECTS OF JOB INSECURITY AND JOB STRESS ON BURNOUT: THE MEDIATING ROLE OF WORKLOAD AMONG EMPLOYEES OF STONE-PROCESSING SMES IN GAMPING VILLAGE, CAMPURDARAT DISTRICT, TULUNGAGUNG - Aisya Ramadhani Eka Aprildianti; Budi Eko Soetjipto; Wening Patmi Rahayu (RADJA PUBLIKA, 2026)
The stone-processing industry is characterized by physically demanding tasks, time pressure, occupational safety risks, production targets, and unstable market demand. This configuration may intensify employees’ job insecurity, stress, workload, and burnout. This study examines the effects of job insecurity and job stress on burnout, both directly and indirectly through workload as a mediating variable. An explanatory quantitative design was employed through a survey of 180 employees working in stone-processing SMEs in Gamping Village, Campurdarat District, Tulungagung. Data were collected using a Likert-scale questionnaire and analyzed through partial least squares structural equation modeling (PLS-SEM). The results indicate that job insecurity has no significant direct effect on burnout (β = 0.004; p = 0.949). Job stress likewise does not directly predict burnout (β = 0.067; p = 0.502). In contrast, job insecurity positively affects workload (β = 0.118; p = 0.047), while job stress exerts a substantially stronger effect on workload (β = 0.633; p < 0.001). Workload significantly increases burnout (β = 0.614; p < 0.001). The indirect-effect analysis identifies workload as a full mediator in the relationship between job insecurity and burnout (β = 0.073; p = 0.048), as well as between job stress and burnout (β = 0.389; p < 0.001). These findings extend the application of Job Demands–Resources theory by positioning workload as the central mechanism through which psychological pressures are transformed into occupational burnout in a labor-intensive industrial setting.